Tiki the cockatoo ebook - Florence, Debbi Michiko (My Furry Foster Family., 2020)
Tiki the cockatoo is the Takano family's newest foster pet and thanks to her ear-splitting screeching, the entire neighborhood knows it! Eight-year-old Kaita has to pull out all the tricks to keep the feathered squawker calm and content and find Tiki a forever home before everyone goes crazy! Giggle-inducing illustrations and 1st-person narration bring this noisy early chapter-book adventure to life.